IMPLEMENTASI SISTEM BASIS DATA UNTUK MENDUKUNG PENGEMBANGAN SISTEM INFORMASI MANAJEMEN SUMBER DAYA MANUSIA (STUDI KASUS : STIKOM DINAMIKA BANGSA) - Mulyadi Mulyadi (LPPM STIKOM Dinamika Bangsa, 2014)
This research is a continuation of previous research based on the analysis and design of human resource management information system that generates a database design and prototype of Human Resource Management Information Systems. This research focused on the implementation of database design into an integrated database system that connects all the functions in order to support the development of HR Management Information System at STIKOM Dinamika Bangsa Jambi. The research was conducted by re-designing the database schema that will be developed by making adjustments to the DBMS needs, design the transactions based on the conceptual schemas and implemented a database system using DDL (Data Definition Language) and DML (Data Manipulation Language) commands.